2017
DOI: 10.3390/ijms18010119
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Endomyocardial Biopsies and Cardiac Manifestations in Taiwanese Patients with the Chinese Hotspot IVS4+919G>A Mutation: Data from the Fabry Outcome Survey

Abstract: We retrospectively evaluated correlations between cardiac manifestations and globotriaosylceramide (Gb3) accumulation in cardiomyocytes from Taiwanese patients with Fabry disease and the IVS4+919G>A (IVS4) mutation who underwent endomyocardial biopsy (Shire; Fabry Outcome Survey data; extracted January 2015). Of 24 males and six females (median age [Q1; Q3] at biopsy 60.4 [57.4; 64.1] and 61.3 [60.4; 65.1] years, respectively), 13 males (54.2%) and five females (83.3%) received agalsidase alfa enzyme replaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The evaluation of ERT efficacy in the late-onset phenotypes with predominant cardiac involvement has been limited to a few small studies in the IVS4+919G>A mutation. In these patients, a significant negative correlation has been described between ERT duration and GB3 accumulation in cardiomyocytes and cardiomyocyte size [ 189 ]. In patients under ERT for more than 3 years, GB3 deposits were not found in cardiomyocytes [ 170 ].…”
Section: Cardiac Treatment In Fdmentioning
confidence: 99%
“…The evaluation of ERT efficacy in the late-onset phenotypes with predominant cardiac involvement has been limited to a few small studies in the IVS4+919G>A mutation. In these patients, a significant negative correlation has been described between ERT duration and GB3 accumulation in cardiomyocytes and cardiomyocyte size [ 189 ]. In patients under ERT for more than 3 years, GB3 deposits were not found in cardiomyocytes [ 170 ].…”
Section: Cardiac Treatment In Fdmentioning
confidence: 99%
“…The presence of fibrosis can be assessed by the amount and distribution of the LGE after gadolinium-based contrast agents administration. Replacement fibrosis is considered a sign of disease progression [ 77 ] and may precede the onset of LVH, particularly in females [ 78 , 79 , 80 ]. Accordingly, by LGE-CMR imaging, fibrosis has been found in both AFD patients with and without LV hypertrophy.…”
Section: Tissue Characterizationmentioning
confidence: 99%
“…FOS has also enabled the study of cardiovascular events in patients with atypical FD (e.g., patients with ISV4 mutations) [ 9 , 10 ]. Compared with patients with classic FD, male (but not female) patients with ISV4 mutations were significantly older when their LVH was initially diagnosed, but no age differences were apparent for other cardiovascular diagnoses [ 10 ].…”
Section: Design History and Evolution Of Fosmentioning
confidence: 99%
“…Endomyocardial biopsy data for 30 patients with ISV4 mutations enrolled in FOS showed that a longer duration of ERT was associated with lower Gb3 accumulation and smaller cardiomyocytes, suggesting a possible impact of ERT on the pathophysiology of the disease. The correlation between Gb3 accumulation and LVMI was statistically significant, but moderate, likely because of the small number of biopsies evaluated [ 9 ]. In addition, retrospective study data showed that there is a reduced risk of thromboembolic events in patients with FD on ERT [ 49 ].…”
Section: Design History and Evolution Of Fosmentioning
confidence: 99%